Decontamination of mycotoxigenic fungi on shelled corn using selective infrared heating technique. Issue 1 (7th January 2021) - Wilson, Shantae A.; Mohammadi Shad, Zeinab; Oduola, Abass A.; Zhou, Zonghui; Jiang, Hongrui; Carbonero, Franck; Atungulu, Griffiths G.
Abstract: Background and objectives: Mycotoxigenic fungi pose a severe threat to humans' health and cause economic losses to crop growers. This study investigated the impact of selected wavelengths of infrared (IR), as a novel technique, followed by a tempering step to inactivate the fungi on shelled corn. Findings: Ascomycota was found to be the most dominant phylum (95.6 and 93.2%, respectively) on corn treated with only IR and IR followed by a tempering. Among fungal genera, Aspergillus was the primary genus found on corn treated with only IR heat. However, a significant reduction in relative abundance of Aspergillus (22%) was obtained when corn with 16% moisture content (wet basis) was treated with the following set up: IR wavelength of 3.2 µm at product‐to‐emitter gap of 110 mm, and 60 s duration. Conclusion: The use of selected IR wavelengths is effective in inactivating mycotoxigenic fungi such as Aspergillus flavus . The further significant suppression of the mycotoxigenic fungi is feasible with incorporating a tempering step into the IR heat treatment. Significance and novelty: The selected IR system is scalable for large scale industrial application, offering promises of reliable and rapid mycotoxigenic fungal inactivation on corn and other cereals.